Synthesis and electrical properties of hydrogen bonded liquid crystal polymer - Korkmaz, Burak; Canli, Nimet Yilmaz; Ozdemir, Zeynep Guven; Okutan, Mustafa; Gursel, Yesim Hepuzer; Sarac, Ayfer; Senkal, Bahire Filiz (ELSEVIER, 2016)
In this study, a new polystyrene based side chain liquid crystalline polymer (EP-PS-LC11)) has been prepared from polystyrene having ethylpiperazine moiety as a hydrogen bond acceptor polymer and 11-(4-cyanobipheny1-4(-oxy)undekan-1-ol (LC11) as a bond donor by molecular self-assembly processes via hydrogen bond formation between nitrogen of ethylpiperazine on polymer chain and hydroxyl group of the LC11. The formation of hydrogen bond has been confirmed by using FTIR spectroscopy. The liquid crystalline behavior of the EP-PS-LC11 has been investigated by a differential scanning calorimeter (DSC) and polarized optical microscopy. The thermal behaviors of the H-bonded liquid crystalline polymer have been investigated by DSC measurements. The dielectric properties and ac conductivity mechanism of EP-PS-LC11 have also been investigated by impedance spectroscopy within the frequency interval of 5 Hz-15 MHz. The dielectric relaxation type of EP-PS-LC11 has been analyzed by fitting dispersion curves of epsilon'-omega). The system obeys nearly Debye and non-Debye type relaxations for the low and high frequency regions. In addition, it has been revealed that since the dielectric strength decreases by increasing frequency, the LC composite molecules can align more easily at high frequency. Moreover, the variation of imaginary component of dielectric constant with frequency shows two relaxation peaks. While the low frequency relaxation peak corresponds to molecular vibration, the high frequency relaxation peak is attributed to molecular orientation. The frequency dependence of ac conductivity has also been analyzed by means of frequency exponent, s. Depending on the frequency deal with, the system exhibit nearly dc, correlated barrier hopping (CBH) and super linear power law (SLPL) behaviors. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Hydrogen bonded liquid crystal polymer; Impedance spectroscopy; Conductivity mechanism; Cole-Cole plot; FREQUENCY-DEPENDENT CONDUCTIVITY; SIDE-CHAIN POLYMERS; DIELECTRIC-RELAXATION; MESOGENIC ACIDS; AC-CONDUCTIVITY; ION DYNAMICS; DESIGN; Chemistry; Physics